THE EFFECT OF HANGMAN GAME ON STUDENTS’ VOCABULARY MASTERY - srimaharani tanjung (JURNAL LINER (Language Intelligence and Educational Research), 2019)
Abstract: The purpose of this research are to find out: 1) the extent of the application of hangman game on students’ vocabulary mastery at the eighth grade of SMP Negeri 1 Padang Bolak. 2)The extent of the students’ vocabulary before and after using hangman game at the eighth grade of SMP Negeri 1 Padang Bolak. 3) Whether there is any significant effect of hangman gameon students’ vocabularymastery at the eighth grade of SMP Negeri 1 Padang Bolak. The population of this research is all of the eight grade Students of SMP Negeri 1 Padang Bolak consists of 103 students. The sample was 25 students which are taken by purposive sampling. The research method is used by experimental method. Then the data is collected by using the instrument. The instrument used is multiple choice. The hypothesis of this research is there is significant effect of hangman gameon students’ vocabulary mastery at the eighth grade of SMPNegeri 1 Padang Bolak. The calculation of ttestformula is higher than score of ttable. The score of the ttestis 18.4 meanwhile the score of ttable is 2,06at 5% significant level with (df) 27, (ttest18.4>ttable2,06) and hypothesis is accepted. It means that there is significant effect of hangman gameon students’ vocabulary mastery at the eighth grade of SMPNegeri 1 Padang Bolak. Keyword: Hangman Game, Vocabulary